Enormous explosion energy of Type IIP SN 2017gmr with bipolar 56Ni ejecta. Issue 1 (13th May 2021) - Utrobin, Victor P; Chugai, Nikolai N; Andrews, Jennifer E; Smith, Nathan; Jencson, Jacob; Howell, D Andrew; Burke, Jamison; Hiramatsu, Daichi; McCully, Curtis; Bostroem, K Azalee
ABSTRACT: The unusual Type IIP SN 2017gmr is revisited in order to pinpoint the origin of its anomalous features, including the peculiar light curve after about 100 d. The hydrodynamic modelling suggests the enormous explosion energy of ≈10 52  erg. We find that the light curve with the prolonged plateau/tail transition can be reproduced either in the model with a high hydrogen abundance in the inner ejecta and a large amount of radioactive 56 Ni, or in the model with an additional central energy source associated with the fallback/magnetar interaction in the propeller regime. The asymmetry of the late H  α emission and the reported linear polarization are reproduced by the model of the bipolar 56 Ni ejecta. The similar bipolar structure of the oxygen distribution is responsible for the two-horn structure of the [O i ] 6360, 6364 Å emission. The bipolar 56 Ni structure along with the high explosion energy are indicative of the magneto-rotational explosion. We identify narrow high-velocity absorption features in H  α and He i 10 830 Å lines with their origin in the fragmented cold dense shell formed due to the outer ejecta deceleration in a confined circumstellar shell.